Analogue images, Rory Gardiner, Maxime Delvaux - Gardiner, Rory ca. 20./21.Jh; Delvaux, Maxime 1984-; Fernández-Abascal, Guillermo; Grau, Urtzi; Woo, Janelle (Perimeter Editions, 2024)
What is the role of contemporary photography in building space? Just where do the dialogues, tensions, and reciprocities between photography and architecture lie? Focusing on the practice of Australian photographer Rory Gardiner and Belgian photographer Maxime Delvaux – two central figures in a new generation of architectural photographers – Analogue Images explores the output of these leading practitioners and poses key questions around the underpinnings and parameters of the broader milieu in which they work. Analogue Images was originally an exhibition at the Tin Sheds Gallery at the University of Sydney, where the work of Gardiner and Delvaux was presented side by side for the first time. The coupling of images disclosed specific nuances in the nature of the photographers’ collaborations, their modes of authorship, and how they captured everyday life. In this book, the initial selection of twenty-two images has been doubled to display a more comprehensive array of work, while texts from photographers, collaborators, and critics situate the images further. The large majority of these pictures are the result of professional commissions. Brussels-based Delvaux is the photographer of choice for Bruther, Baukunst, 51N4E, Muoto, and Christian Kerez, whereas Gardiner, who is based in Melbourne, is for Baracco+Wright, Richard Stampton, Candalepas Associates, Buchner Bründler Architekten, and Ludwig Godefroy. Their images are the lenses through which we consume a big chunk of contemporary architecture. As such, Analogue Images is both an attempt at a critical analysis of their work and a collection of some good architecture
First edition of 1000
Keywords: Gardiner, Rory -- ca. 20./21.Jh.; Delvaux, Maxime -- 1984-; Fotografie; Sydney -- Motiv; Gardiner, Rory; Delvaux, Maxime; Photography, Artistic; Photographie artistique; art photography; Bildband